IMPLEMENTASI WALL STORY “FOUR MAGIC WORDS: THANKS, EXCUSE ME, HELP AND SORRY” DI KELAS V UPT SDN 3 PRINGSEWU SELATAN - Mulati, Dyah Fitri (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2024)
This Community Service Activity (CSA) implements Wall Story to improve English speaking skills and develop the character of students at UPT SDN 3 Pringsewu Selatan, Pringsewu Regency, Lampung. This program begins by providing material about the Four Magic Words, namely thank you, please, sorry, and excuse me. Then, students will be divided into groups to work together to compose the story wall. The activity method used is in the form of teaching and assistance in preparing wall stories and presenting the results of lectures in groups. The process of Community Service activities will be carried out at UPT SDN 3 Pringsewu Selatan for three weeks, which will be held on 13 – 31 May 2024. With this PKM program, it is expected that students will be able to improve their speaking skills in English in an active and enjoyable way and be able to develop good character through the four magic words (thank you, please, sorry, and permission).